Participant Observation and Research on Fitness “Daily Attendance” in the Context of Social Media - Peng, Xiangquan (Transactions on Social Science, Education and Humanities Research, 2024)
The "fitness fever" emerging in social media platforms has attracted a large number of users to participate in “daily attendance”. Based on participant observation, questionnaire survey and other empirical research methods, this study observes the users who participate in fitness “daily attendance” and webcast influencers who organize fitness “daily attendance”, so as to analyze their behavior characteristics in the context of social media. This paper finds that during the participation in fitness “daily attendance”, webcast influencers actively interact with users and make efforts in agenda setting, participation motivation and communication content, thus clarifying the logic behind the fitness “daily attendance”.